The China record : an assessment of the People's Republic - Wang, Fei-Ling (State University of New York Press, 2023)
"Detailed assessment of the People's Republic of China as an alternative mode of political system and as a distinctive model of socioeconomic development"-- Provided by publisher.
Keywords: China -- Politics and government -- 1949-; China -- Economic conditions -- 1949-; China -- Civilization -- 1949-; Chine -- Politique et gouvernement -- 1949-; Chine -- Conditions économiques -- 1949-; Chine -- Civilisation -- 1949-; POLITICAL SCIENCE / Political Ideologies / Communism, Post-Communism & Socialism.; Civilization; Economic history; Politics and government; China; Since 1949